2021
DOI: 10.1021/acsanm.1c01233
|View full text |Cite
|
Sign up to set email alerts
|

Porous Ni Foams Filled by N-Doped Carbon Nanotubes Coated with N-Doped Ni3P and Ni Nanoparticles for Catalytic Water Splitting

Abstract: The development of bifunctional catalysts possessing high efficiency and excellent stability was still a challenge as regards overall water splitting. Herein, a reasonable space division strategy of Ni foam (NF) was proposed to design a bifunctional catalyst. Ni-P alloy was loaded on carbon nanotubes (CNTs) through Pd-free electroless plating (Ni-P/CNTs). Subsequently, the Ni-P/CNT catalysts mixed with melamine were annealed for N doping. The N-doped CNTs coated with N-doped Ni3P and Ni nanoparticles (N-Ni3P-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Figure 3 (e) shows the N 1s orbital spectrum. After Gaussian tting, it is found that there are mainly two forms of nitrogen, namely pyridine nitrogen at 399.4 eV and graphite nitrogen at 401.3 eV [24]. The C 1s spectrum (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…Figure 3 (e) shows the N 1s orbital spectrum. After Gaussian tting, it is found that there are mainly two forms of nitrogen, namely pyridine nitrogen at 399.4 eV and graphite nitrogen at 401.3 eV [24]. The C 1s spectrum (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…As shown in Figure b, the cell voltages can provide an overpotential as low as 1.697 V at the CD of 100 mA cm –2 in 1 M KOH alkaline conditions at room temperature, and 1.724 V at 100 mA cm –2 CD in alkaline simulated seawater. The performance of most non-precious metal electrolytic cells cannot do this (Figure c), as well as the precious metal catalyst electrolytic cell composed of commercial Pt/C//RuO 2 under the same conditions. In particular, our electrolytic cells can generate a large CD of 300 mA cm –2 in alkaline simulated seawater (1 M KOH + 0.5 M NaCl) electrolyte at a voltage of 1.822 V, which is satisfactory to realize application for large current density at low voltage industrially.…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, the synergistic effect of the graphene and bimetallic sulfides was observed when the heterojunction established. The impact of dual N doping on the support, and transition metal compound was also examined to employ the N for adjusting the electronic structure of both ingredients [18b] . In this report, N‐CNT coated with N‐doped Ni 3 P and Ni nanoparticles (NPs) promoted the electrochemical water splitting, by which overpotentials of 73, and 270 mV for HER, and OER were resulted.…”
Section: N‐doped Electrocatalysts For Water Splittingmentioning
confidence: 97%
“…Post‐treatment N doping is the insertion of N after the creating electrocatalyst, which is carried out by one of the N saturations (type III) or thermal decomposition of the loaded N source (type IV). In type III, contacting excess amounts of N source leads to the doping of N atoms on the surface of the materials; in particular, N 2 and ammonia have been widely employed, such as annealing modified CNT under N 2 for the production of N‐CNT [18b] . Type IV is the most versatile strategy for N doping since abundant N‐containing materials could be uploaded on the desired compounds and subsequently decomposed by thermal treatment to leave N. For example, the NG part of MoS 2 −NiS 2 /NG was synthesized via immersing melamine sponge as the N source into GO suspension and burning the leached GO with melamine [16b] .…”
Section: N‐doped Electrocatalysts For Water Splittingmentioning
confidence: 99%